Bayang-Bayang Kafala Pasca-Reformasi Qatar: Kritik Hukum Kebiasaan Internasional terhadap Penegakan Hukum Selektif atas Pekerja Migran - Nawal Alifiah Hidayat; Zerry Akbar Yudisetyo (Jurnal Interpretasi Hukum, 2025)
The paper will observe the post-kafala labor law reforms in Qatar concerning the binding principles of customary international law. Through the juridical-normative approach, the study assesses Qatar based on the adherence to three fundamental customary norms such as freedom of movement, non-discrimination, and due process since the 2020 legislative changes that formally ended the sponsorship system. The results indicate that the highly-rated reforms such removal of exit permits, introduction of minimum wage, among others, are still more of a form, whereby, procedures and administrative processes keep the gist of dependency. The continued violation of universal customary norms is evidenced by such persistent obstacles as a 90-day notice period, Arabic-only grievance procedures, and the differential enforcement of the same based on nationality. The paper advances the notion of the Shadow of Kafala which explains how Qatar manages to maintain structural control and selective implementation in the name of compliance. The study paves the way in international law by entrenching customary law as a normative reference point in the assessment of labor reforms outside the treaty ratification. Besides, it offers a legal basis on which the labor sending states can invoke the state responsibility pursuant to the erga omnes obligations in case of systematic discrimination and deliberate enforcement.